2006
DOI: 10.1016/j.febslet.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate‐induced modulation of cell membrane. VIII. Agglutination with mammalian lectin galectin‐1 increases osmofragility and membrane fluidity of trypsinized erythrocytes

Abstract: Interaction of lectins with cell surface determinants may alter membrane properties. Using trypsinized rabbit erythrocytes as model we tested the capacity of an endogenous lectin in this respect. Galectin-1 is a member of an adhesion/growthregulatory family known to interact for example with ganglioside GM 1 and also the hydrophobic tail of oncogenic H-Ras. Assays on membrane fluidity and osmofragility detect galectin-1's capacity to increase the parameters. Moreover, it increases susceptibility of erythrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This membrane destabilization could be due to the lectin-like behaviour of CRP [16,45]. Thus CRP when added exogenously will cross-link with the membrane surface receptors leading to lateral molecular reorganizations in the plane of the bilayer [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…This membrane destabilization could be due to the lectin-like behaviour of CRP [16,45]. Thus CRP when added exogenously will cross-link with the membrane surface receptors leading to lateral molecular reorganizations in the plane of the bilayer [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Besides these analyses, the study of osmotic fragility of RBC is also very relevant (Gupta et al, 2006;Panis and Souza, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ionescu-Zanetti et al (2005) studied changes in the morphology of individual cells during membrane porationdriven hemolysis providing an explanation for increased RBC-OF in patients who have spherocytosis. Gupta et al (2006) observed the potential of endogenous lectin to affect membrane properties such as OF beyond the immediate interaction with cell surface epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations